Perancangan Sistem Informasi Berbasis Web Pada PT.Sheshi Kreatif Indonesia Menggunakan Metode Agile - Safitri, Lingga; Fadhil Fathoni, Muhammad; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This research aims to design and implement a web-based information system for PT. Sheshi Creative Indonesia to improve operational efficiency and data accuracy. The system was built using the Agile method, which emphasizes flexibility, team collaboration, and continuous iteration in software development. The main problem faced is the management of flower sales data which is still manual, has the risk of losing data, and is less efficient. The proposed system includes online ordering features, product and category management, and increased data security. With this implementation, customers can easily place orders through a responsive platform, while companies can manage inventory more effectively. Testing is carried out using the black-box method to ensure all features work according to specifications. The results show that this system is able to speed up operational processes, increase customer satisfaction, and minimize errors due to manual recording.